HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PASIEN GANGGUAN JIWA - Marjes N. Tumurang (Politeknik Kesehatan Kemenkes Sorong, 2023)
Patients with mental disorders must take medication continuously so that patients can be prevented from relapse. The family as a caregiver plays an important role in supporting patient compliance by providing motivation to take medication. This study aims to determine the relationship between family support and medication adherence in patients with mental disorders in the Working Area of the Gogagoman Health Center. The research method uses a research design that is descriptive analytic using cross sectional method. The number of samples in this study were 35 respondents. The sampling technique used is the total sample. The results of the research using the chi square test value P value = 0.000 or